Magneto-active Slosh Control - Carls, Liam Serafino; Bossong, Cassandra Christina (Proceedings of the Wisconsin Space Conference, 2022)
The Magneto-active Slosh Control (MaSC) project seeks to demonstrate active slosh control in cylindrical propellant tanks by means of a thin, flexible metallic membrane that is acted on by a magnetic field in order to reposition itself to produce an optimized force on the surface of the liquid. Slosh is a destabilizing effect of engine burns and other orbital operations. The mitigation of slosh is a mission-critical effort in the aerospace industry. The overall objectives for the Magneto-active Slosh Control experiment are to demonstrate slosh control forces on liquid surfaces exerted by a high-permeability magnetic membrane in an external magnetic field, as well as develop active sensing and control of the membrane's position in microgravity environments.